Hallazgos de Trichonoma gallinae (Rivolta, 1878) en la paloma domestica (Columba libia domestica) - Hernandez, M.=700 1 Larramendy, L.; Szczypel, B.
(Es, En)
Ilus., 5 ref.
Keywords: PALOMA; TRICHOMONAS; PARASITOS; CUBA; TRICHOMONA GALLINAE; REVISTA CUBANA DE CIENCIA AVICOLA